Pathological Investigation of Dying Mimusops Elengi Linn. Avenue Trees in Assam - Choudhury, Reeta; Dubey, R. M. (Indian Forester, 2013)
Mimusops elengi Linn. is a member of family Sapotaceae and is one of the best plants recommended for avenue plantation because of its scented flowers, edible fruits, medicinal uses and dense crown. The present study was undertaken to find out the cause of mortality in M. elengi trees. A total of 60 inocula from affected root samples collected from dead trees were plated which yielded a total of 72 fungi. Two types of fungi were isolated, of which Ganoderma applanatum was found dominant based on colony features of the cultures and their morphologies.